An Investigation into the Critical Factors’ Impact on Digital Technology Transformation in Taiwanese Family Enterprises - Thi-Them Hoang; Yung-Fu Huang; Manh-Hoang Do (Journal of Theoretical and Applied Electronic Commerce Research)
The study aims to evaluate the factors influencing digital technology transformation in Taiwanese family companies. Data were obtained from nine Taiwanese experts with extensive expertise in family businesses and analyzed using the TOPSIS approach. The research findings identify twelve essential factors that influence digital technology transformation and provide the best recommendations for organizations. The study identified and analyzed four key elements deemed most critical in influencing the digital transformation of Taiwanese family businesses: education and training, technological complexity, technological advancements, and management support. Importantly, the organizational group is the primary driver of digital transformation through the case of Taiwanese family enterprises. This study adds to the existing literature by identifying the most essential criteria and ranking them. The Taiwanese family enterprises should use this model cautiously, considering the potential relationships among group factors in the TOE model. Moreover, the findings also offer potential suggestions for policymakers to enhance the integration of digital technologies across all facets of society and business.